Integration of community structure data reveals observable effects below sediment guideline thresholds in a large estuary. Issue 9 (13th April 2017) - Tremblay, Louis A.; Clark, Dana; Sinner, Jim; Ellis, Joanne I.
Abstract : Multivariate analysis detected changes in benthic community structure below guideline levels for three metals in a large estuary. Abstract : The sustainable management of estuarine and coastal ecosystems requires robust frameworks due to the presence of multiple physical and chemical stressors. In this study, we assessed whether ecological health decline, based on community structure composition changes along a pollution gradient, occurred at levels below guideline threshold values for copper, zinc and lead. Canonical analysis of principal coordinates (CAP) was used to characterise benthic communities along a metal contamination gradient. The analysis revealed changes in benthic community distribution at levels below the individual guideline values for the three metals. These results suggest that field-based measures of ecological health analysed with multivariate tools can provide additional information to single metal guideline threshold values to monitor large systems exposed to multiple stressors.